Four-stranded coiled-coil elastic protein in the byssus of the giant clam, Tridacna maxima - Miserez, Ali (2013)
An elastic protein with a secondary structure distinct from all well-known load-bearing proteins is found in the byssus of the giant clam, Tridacna maxima. The byssus consists of a bundle of hundreds of individual threads, each measuring about about 100 μm in diameter, which exhibit a tendon-like mechanical response. The amino acid composition of Tridacna byssus, however, is unlike tendon collagen, lacking high glycine, proline, and hydroxyproline. Wide-angle X-ray scattering (WAXS) and small-angle X-ray scattering (SAXS) measurements suggest that the constituent nanofibrils of the byssal threads are distinct from known secondary structure motifs previously reported for elastic proteins including the collagen triple-helix, the β-sheet nanocrystalline domains of silks, or the double-stranded coiled-coil regions of intermediate filaments. Instead, X-ray diffraction data indicate a structural organization in which four coiled-coil α-helices form a stable rope-like structure, which then further pack in a pseudohexagonal lattice to form nanofibrils. Amino acid composition analysis shows unusually high concentrations of acidic as well as basic residues, suggesting that the four-helix structure is stabilized by strong ionic interactions between oppositely charged residues in neighboring strands. The composition also suggests additional stabilization by disulfide cross-linking. On a larger scale, scanning and conventional transmission electron microscope (STEM and TEM) observations indicate that the nanofibrils exhibit an alternating periodicity of about 500 nm along the axial direction. A molecular model that combines the mechanical properties with the structural characteristics of the Tridacna byssal threads is proposed.